Mind the subtle f0 modifications: The interaction of tone and intonation in Sinitic varieties - Chen, Yiya (Stellenbosch Papers in Linguistics Plus, 2022)
Sinitic varieties are well known for their complex lexical tone systems. Lesser known is that these varieties also employ intonation for multiple communicative functions, ranging from indexing a speaker’s socio-cognitive information (such as emotions and attitudes) to signaling various linguistic information (such as asking questions, marking focus, and encoding prosodic structure). This paper reviews the multiplexing of lexical tone and intonation into the same melodic f0 signal. The main empirical focus is on Standard Chinese; whenever possible, comparisons are made across Sinitic varieties (such as Shanghai Wu Chinese and Cantonese). I will show that lexical tone constrains the changes of f0 for intonation. How tone and intonation interact, however, varies across communicative contexts and language varieties, which is also reflected in how listeners utilize the f0 information to decode the melodic pitch signal during speech processing. From a cross-linguistic viewpoint, findings on intonation in Sinitic varieties suggest 1) the need for detailed acoustic and perceptual studies to understand the subtle f0 modifications for intonation in tone languages, and 2) the importance of a comparative approach to understanding the similarities and differences of intonation in tone languages.